Sharia Perspective on QRIS-Based Mosque Donations Funded by Conventional Credit Cards: An Analytical Study of Contracts and Validity in Fiqh Muamalah - Dwi Setyo Wiratomo (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2026)
This research explores the Sharia perspective on using QRIS as a digital payment platform for mosque donations, especially when funds come from conventional credit cards. As Indonesian mosques increasingly embrace QRIS to support digital philanthropy, ethical and legal questions emerge about transaction validity under Islamic law, particularly regarding riba involvement and public trust. Using a fiqh muamalah approach, the study analyzes the contractual structure behind QRIS transactions funded by conventional credit cards through doctrinal legal analysis, DSN-MUI fatwa review, and semi-structured interviews with mosque administrators and Islamic finance scholars. Findings reveal that while QRIS improves convenience and transparency, conventional credit cards introduce riba risks and sharia compliance uncertainty. Existing fatwas permit such payments only when no interest is charged, highlighting the need for digital systems ensuring transactions remain halal. The study concludes that stronger sharia governance, transparency, and public awareness are essential for maintaining ethical and trustworthy donation practices in the digital era. This research contributes to sustainable Islamic business practices, responsible digital finance, and ethical philanthropy, offering practical recommendations for mosque leaders and policymakers to harmonize technology with Islamic law while supporting the Sustainable Development Goals (SDGs).